Open-globe repairs among Medicare beneficiaries from 2011 to 2020 - Ali, Muhammad; Dun, Chen; Justin, Grant; Makary, Martin; Woreta, Fasika (Digital Journal of Ophthalmology, 2024)
Introduction The purpose of our study is to evaluate the characteristics of patients undergoing open-globe repairs (OGR) and surgeons performing these surgeries across the United States. Methods We used 100% Medicare Fee-For-Service dataset from 2011 to 2020 for eyes of patients ≥18 years who underwent OGR. Current Procedural Terminology (CPT) codes (65275, 65280, 65285, 65286, 65235, 65260, and 65265) were used to identify OGR. Patient characteristics, including age, sex, race, ethnicity, Charlson comorbidity index, location of surgery, median income based on zip code, census region, and population density were evaluated using χ2 goodness of fit test. Ocular trauma surgeon was defined as an ophthalmologist who performs ≥1 OGR in a calendar year. Surgeon characteristics were stratified by sex and compared using χ2 and t test. They included census region of practice, population density of practice, years since medical school graduation and annual OGR volume. A P value of <0.05 was considered statistically significant. Results A total of 16,576 patients with a mean age of 73.89 ± 12.89 years underwent OGR. Most patients were White (79.68%; n = 13,207; P < 0.001) and 49.44% (n = 8196) were female (male, n = 8380, 50.56%; P = 0.15). More patients resided in a rural area (18.71%; n = 3102) relative to surgeon location (4.51%; n = 748; P < 0.001). A total of 5,898 surgeons performed these surgeries with 77.33% (n = 4,561) male and 22.67% (n = 1,337) female surgeons. Male surgeons performed most of the surgeries (76.35%; n = 12,655; P < 0.001). On average a surgeon performed a single OGR annually (mean, 1.08 ± 1.04; range, 0.11-40). Conclusions There are fewer ocular trauma surgeons within the rural United States and fewer female ocular trauma surgeons. Future studies are needed to assess the impact of these differences on patient outcomes.